(untitled) (LACCEI, 2024)
The main objective of this study was to determine how digital marketing influences the consumer behavior of the Uber brand, Lima Metropolitana 2021. In that sense, a non-experimental methodological design of cross-sectional, quantitative approach and explanatory level was used, considering as the study population the inhabitants of the city of Metropolitan Lima between the ages of 18 to 55 years old, considering a sample of 385 people. Therefore, the survey technique was used through the questionnaire as an instrument for measuring the variables, on an ordinal Likert-type scale, which presented a high level of overall internal consistency (Cronbach’s alpha = .983) and content validity by expert judgment (Aiken’s V = 1.00). It was concluded at a general level that digital marketing does significantly influence consumer behavior of the Uber brand, Lima Metropolitana 2021, demonstrated through Pearson’s Chi-square inferential test, with a confidence level of 95% and a significance of 0.000, which confirms that consumer behavior of the Uber brand is explained by the possible actions or influence of digital marketing.